Iron Resources and Production for the Roman Frontier in Pannonia - Durman, Aleksandar (2002)
During Roman times Siscia was an important settlement, controlling a key route between Pannonia and Dalmatia, across the river Sava. To the south of Siscia, on Mount Trgovi, Mount Zrin and Mount Majdan, limonite deposits were exploited on a very large scale resulting in millions of tons of slag. Finds of large number of iron bars from Hrvatska Dubica, Siscia and the Japra valley indicate extensive iron smithing in the area. 38 of these bars survive and their size and weight suggest a degree of standardisation of the products. It is estimated that between 150 to 200 million of these bars would have been produced in this region during the Roman period.
Projekt MZOS
ENG